(untitled) (Global Journal of Medical Research, 2021)
A method for numerical stress analysis with multiple advantages of being applicable to solids of irregular geometry that contain heterogeneous material properties is finite element method. This analysis provides with quantitative data that can extend the understanding of physiologic reactions that occur within the dentoalveolar complex.